The doctrine of ultra vires s.its reform under section 20 of the Malaysian companies act 1965 / Daud Abdul Majed - Abdul Majed, Daud (Faculty of Law, 1983)
without assistance, co-operation and understanding from Mr.U.K. Menon, Koordinator Undang-Undang, MARA Institute of Technology, Shah Alam. I am deeply indebted to him who has devoted a great deal of time and energy throughout the preparation of this paper. He has assisted me immensely in my research and with the checking the whole of the proofs. A number of changes had been made in pursuance to his valuable suggestions.